An Overview of Mental Health on Stress Among Students In USM - Rana, Nurdiana Binti Md Masud; Rayeesudeen, Nuramirah Binti; Jalil, Nurdyana Aqylah Binti Abdul; Abideen, Nurashira Binti Mohamed Zainul (AIBPM Publisher, 2023)
Mental health of higher education students is deteriorating at an alarming rate. The Covid-19 pandemic has had a severe psychological impact on students, who are constantly burdened with various learning tasks as well as online lectures. This study explains the influencing factors that affect the mental health of students in Universiti Sains Malaysia (USM). We conducted an online survey via Google Forms. A total of 150 USM students participated in the online survey. The data gained was interpreted using IBM SPSS Statistic Software to produce meaningful results. The potential causes of stress among USM students that will be discussed briefly in this research are health issues, academic problems, financial difficulties, and family problems. We also consider the Covid-19- pandemic effects on the factors elaborated in this research. Stress can be treated and must be well managed so that it will not become worse. There are many ways and activities that can be done to avoid being stressed.